Perampokan Dalam Perspektif Hukum Pidana Islam - Nur Najwa; Nabila Anggraini; Herlina Herlina; Surya Sukti (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
. Robbery (hirâbah) in Islamic criminal law (fikih jinayah) is defined as the act of taking someone else's property forcibly and openly on a public road by using violence or the threat of violence. Hirâbah is classified as jarîmah hudud because the type and punishment are strictly determined by shara'. Proof of jarîmah hirâbah in Islamic criminal law is based on the perpetrator's confession (iqrâr), testimony (shahâdah), and strong clues/indications (qarînah) that lead to the occurrence of the jarîmah. Legal sanctions for the perpetrators of hirâbah have been stipulated in the Quran surah Al-Maidah verse 33, which consists of the death penalty, crucifixion, cross-cutting of hands and feet, and exile / imprisonment.